Fluorodeoxyglucose positron emission tomography–computed tomography missed tibial metastasis in head and neck cancer: a case report and review of literature - Hamidreza Movahedi; Lena Nazemi; Saina Ghadiany; Alireza Movahedi; Farzad Dehghani Mahmoudabadi; Mohammadhossein Aghazadeh; Seyed Esmaeil Mousavi; Shaghayegh Khodabakhshian (Journal of Medical Case Reports)
Abstract Introduction Head and neck squamous cell carcinoma is the seventh most common type of cancer in the world. Metastases occur in up to 40% of cases, and bones are the second most frequent site. Metastases in extremities are uncommon, with very few publications covering distal lower-limb bone metastasis. Case presentation Here we report the case of a 47-year-old Persian man with head and neck squamous cell carcinoma managed by induction chemotherapy, surgery, and adjuvant chemoradiotherapy. During the adjuvant treatment, the patient experienced right tibial pain, with additional workup revealing a distal lower-limb bone metastasis that had remained undetected during the standard workup for head and neck squamous cell carcinoma. Discussion In current guidelines, recommended fluorodeoxyglucose positron emission tomography–computed tomography in head and neck squamous cell carcinoma does not extend below the popliteal fossae. The undetected metastasis led to overtreatment of this patient. Systematic review of literature showed only six cases of distal lower-limb metastasis from head and neck cancer, which are eligible for discussion. Conclusion Although rare, physicians should keep in mind that as recommended fluorodeoxyglucose positron emission tomography–computed tomography does not extend below the popliteal fossae, metastases may be missed, potentially leading to overtreatment.